ANALISA PERENCANAAN STRATEGIS PENGELOLAAN SDM PADA PDAM TIRTA PAKUAN KOTA BOGOR - Abdul Gani (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
Every company is attempting to reach the objective and performance’s goal that has been determinedbefore with the human resources organization. Getting the aim of the organization achievement is used tomeasure the success of management and employee. To bring about the company vision, mission, objective andstrategy that will be achieved in long period requires the integrated management system between humanresources organization and functional strategic planning system of human resources management so t hatstrategy of implementation planning can be reached optimal likewise Water Supply Company Owned by LocalGovernment ( PDAM) as a general service business that give the top priority in satisfied service for society willbe influenced by the accuracy in formulating the strategy operated by management, therefore the writerdecides to write this paper with tittle “ Strategic Planning for Human Resources Management in PDAM TirtaPakuan Kota Bogor”. Based on the existing condition of PDAM as observation object the case is: What process and problemfaced in the implementation of strategic planning for human resources management in PDAM Tirta PakuanKota Bogor. That at used the writer used some research instruments such as questioners that have beendisseminated in all chairmen in PDAM. There are 39 responses which the examination analysis use by CFA(confirmatory factor analysis), but the writer also use the business strategic model by J. David Hunger &Thomas L Wheelen and Integrated of Performance Human Resources Management System based on balancedscorecard by Mulyadi. There are four main factors which have to got important role in strategic planning system, theya are:(i) human resources competence as a factor to determine strategic planning, then, (ii) performance assessment,employee satisfaction and functional strategic planning. Based on the environment analysis and SWOT analysis, the company is situated in 3 quadrant thatcan be interpreted is growing phase. In spite of the result score ia regarded as the low growth rate relatively. Itis significant to find the weakness of internal human resources with the achievement of strategic planning offunctional human rescorces management. Indication of that case has not been the performance assessmentsystem for employee based on actual performance. The other solution for this case faced by a company,recommended in strategic planning arrangement process use approach by the integrated management systemwith a perspective balanced scorecard, as one of a management instrument to evaluate how succesfull are themission, vision, objective and goals. Besides the integration is available in arranging of strategic planning ofhuman resources management, it is done by strategy map to be used as the arrangement of the establishmentprogram and employee development